How Subtle Changes Can Make a Difference: Reproducibility in Complex Supramolecular Systems. Issue 41 (5th September 2022) - Schnitzer, Tobias; Preuss, Marco D.; van Basten, Jule; Schoenmakers, Sandra M. C.; Spiering, A. J. H.; Vantomme, Ghislaine; Meijer, E. W.
Abstract: The desire to construct complex molecular systems is driven by the need for technological (r)evolution and our intrinsic curiosity to comprehend the origin of life. Supramolecular chemists tackle this challenge by combining covalent and noncovalent reactions leading to multicomponent systems with emerging complexity. However, this synthetic strategy often coincides with difficult preparation protocols and a narrow window of suitable conditions. Here, we report on unsuspected observations of our group that highlight the impact of subtle "irregularities" on supramolecular systems. Based on the effects of pathway complexity, minute amounts of water in organic solvents or small impurities in the supramolecular building block, we discuss potential pitfalls in the study of complex systems. This article is intended to draw attention to often overlooked details and to initiate an open discussion on the importance of reporting experimental details to increase reproducibility in supramolecular chemistry. Abstract : The synthesis of complex systems often coincides with difficult preparation protocols and narrow windows of suitable conditions. In this Scientific Perspective, we report on unexpected observations made in our group that highlight the impact of subtle "irregularities" on supramolecular systems. We draw attention to often overlooked details and aim to initiate an open discussion on reproducibility in supramolecular chemistry.